تطبيق نظرية هيرمينوتيك لهانس جورج جادامر على حديث النبي محمد: HANS-GEORG GADAMER'S HERMENEUTIC CONCEPTS AND ITS APPLICATIONS IN UNDERSTANDING THE PROPHET'S HADITH - Ajeng Ayu Almaratis Soliha Ilham (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
ABSTRACT The hadiths of the Prophet are present in people's lives today in a 'frozen' form and have no application. This has prompted the initiation of various breakthroughs to find a way out of the coldness for the 'native' hadith to conform to the demands of the times. One of them is through the hermeneutic approach in the interpretation of hadith. The hermeneutic approach in the interpretation of hadith can be taken through three layers of interpretation, namely: 1. Interpretation "from within" the hadith text. 2. Interpretation of the "environment" of the hadith text. 3. interpretation "against" the hadith text. From the above interpretation has a focus, objectives and methods from one another. This method is not only a tool for studying the horizon of the text (matan), but also the horizon of the initiator (Prophet), the reader (rijal al-hadith, mukharrij al-hadith, and mufassir), and their contextuality. Although hermeneutics is a "tool" (not a substitute for) various well-established hadith sciences, the hermeneutic approach is expected to produce meanings that combine elements of hadith textuality and contextuality at the same time, considering that text can only find meaning in context. Keywords: Hermeneutic, Native, Frozen